Localization of vascular endothelial growth factor and transforming growth factor-β in tissues in perifractural zone after fractures of long bones of limbs in humans - Grigoryev, Vitaliy; Popsuishapka, Olexii; Ashukina, Nataliya; Galkin, Fedor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Objective: to study, using immunohistochemical methods, the content of the vascular endothelial growth factor and transforming growth factor (TGF-β) in tissues adjacent to bone fragments after fracture in humans, as well as in autofibrin obtained in vitro. Methods: biopsy samples (interfragmental fibrin-blood clot, periosteum, muscular and fatty tissue), 9 of the victims recovered from the near fracture zone with fractures of limb bones during their open comparison were studied. In addition, fibrin-blood clots from the venous blood of the same patients obtained during the operation by the method of J. Choukroun were analyzed. Results: 1–2 days after the fracture, vascular endothelial growth factor concentrates in fibrin, forming a fibrin-blood clot in the near-fracture zone. On the 5th–12th day, the intensity of the reaction to vascular endothelial growth factor in fibrin decreases, or it disappears, and expression of the factor manifests itself in the cells of the regenerate — osteocytes, osteoblasts, fibroblasts, endotheliocytes. 10–12 days after injury, a positive reaction to vascular endothelial growth factor is defined in endotheliocytes and osteoblasts. The reaction to TGF-β in fibrin-blood clot and regenerate tissues was observed exclusively in cells. In autologous fibrin clots, vascular endothelial growth factor expression was observed in fibrin, and TGF was observed in the blood cells that remained in it. However, the intensity of the response to vascular endothelial growth factor in fibrin formed in vitro was uneven. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> vascular endothelial growth factorconcentration on the 1–2 day after fracture in the fibrin-blood clot in the near fracture zone is a strong signal for the restoration of blood supply in the area of injury. Expression of TGF-β at all times was found only in cells. The uneven distribution of vascular endothelial growth factor in fibrin formed in vitro should be considered when it is used to optimize bone repair.